2020
DOI: 10.2169/internalmedicine.3811-19
|View full text |Cite
|
Sign up to set email alerts
|

Sitosterolemia Exhibiting Severe Hypercholesterolemia with Tendon Xanthomas Due to Compound Heterozygous <i>ABCG5</i> Gene Mutations Treated with Ezetimibe and Alirocumab

Abstract: We herein report a rare case presenting with severe hypercholesterolemia, massive Achilles tendon xanthomas, and multi-vessel coronary artery disease. Initially, the patient was misdiagnosed with familial hypercholesterolemia. However, a genetic analysis using our custom sequencing panel covering genes associated with Mendelian lipid disorders revealed him to have a genetic basis of sitosterolemia with compound heterozygous mutations in the adenosine triphosphate binding cassette subfamily G5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Therefore, a dysfunction caused by genetic mutations will lead to elevated serum sterol levels. Sitosterolemia caused by critical biallelic genetic mutations is a recessive disorder characterized by extremely high LDL cholesterol and sitosterol levels (11)(12)(13)(14)(15)(16)(17)(18). However, there are emerging data showing that a single mutation in ABCG5 can exceed the clinical threshold, and this is referred to as hyper LDL cholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a dysfunction caused by genetic mutations will lead to elevated serum sterol levels. Sitosterolemia caused by critical biallelic genetic mutations is a recessive disorder characterized by extremely high LDL cholesterol and sitosterol levels (11)(12)(13)(14)(15)(16)(17)(18). However, there are emerging data showing that a single mutation in ABCG5 can exceed the clinical threshold, and this is referred to as hyper LDL cholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PCSK9 inhibitors on sitosterol levels has not yet been established. A few studies have reported the effectiveness of PCSK9 inhibitors in patients with sitosterolemia, especially those with high levels of cholesterol (33,34). Thus, statins and PCSK9 inhibitors can be considered treatment options for patients with very high lev- 47 .…”
Section: Discussionmentioning
confidence: 99%
“…These include elevated LDL cholesterol levels, cutaneous xanthomas since childhood, and premature CAD in childhood. 89 90 91 We have managed worse cases of sitosterolemia with premature CAD, a case of a young lady (aged 25 years old) with myocardial infarction, 89 and a boy (aged 15 years old) with ischemic heart failure. 91 Both patients had cutaneous xanthomas and Achilles tendon thickness similar to HoFH.…”
Section: Factors Contributing To the Phenotypic Variations Of Fhmentioning
confidence: 99%